Exploring Listening Skills and Motivation for Autonomous Learning with TED Talks: Does It Have an Effect? - Jafna Ahsana Fadya R; Afina Faza Ivanda; Hana Resya Anindya; Mutia Rahmawati; Neneng Sunengsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Listening skills are rarely emphasized in English classes compared to other skills so there is a need for additional media such as TED Talk. Moreover, it is still rarely used as a learning medium in high school. Therefore, this research aims to investigate secondary school students' responses using TED Talks for their motivation to improve listening skills autonomously. This research uses qualitative methods with questionnaires using Google Forms and Focus Group Discussions using Zoom or Google Meet. The sampling was conducted randomly with 10 participants from class XII students at SMAS Dua Mei in South Tangerang. This study analyzes students' knowledge and perceptions of TED Talk videos as autonomous learning media in listening skills. The researchers are interested in exploring how TED Talk can help students' motivation for autonomous learning and their interest in learning by listening after watching it. The results showed that some students still needed to familiarize themselves with TED Talks. Their responses became more positive after watching the video. Videos that balance an interesting speaker with various expressions, relevant topics, and audio-visual aspects are more likely to be well-received by students. They believe that TED Talks as supplementary material can improve listening skills by motivating them to learn autonomously.